Exploring pull and push factors influencing human resources in two South African Health facilities - Sohaba, Nkosinathi (My University, 2013)
Study Title: Exploring Pull and Push Influencing Human Resources at two South African Health Facilities Introduction The magnitude of the health worker shortage in developing countries such as South Africa cannot be overstated and requires an urgent, sustained and coordinated response. In South Africa, the government has introduced many initiatives, such as the rural allowance, to attract more health practitioners in rural areas. However, human resource shortages remain a challenge and therefore looking at ways to better utilize the capacity of human resources could play a significant role in addressing this problem, and could contribute to establishing a well-functioning public health system. Objectives This study was aimed at exploring and describing factors that affect human resource capacity in two district hospitals in the Eastern Cape Province: one rural, one urban, and makes appropriate recommendations to health authorities so as to better utilize and retain human resource capacity within the facilities. Methods This is a qualitative study, using explorative and descriptive research strategies. The study was conducted in two district hospitals, one urban (hospital B) and one in a rural area (hospital A), both in the Eastern Cape Province. A total of thirty six in-depth interviews were conducted with allied health professionals and administrative staff – eighteen from each site - to explore their perceptions around “pull and push factors” in their work. Additionally, four interviews were conducted with district team members and key policy documents were reviewed. Results The availability of equipment, and quality of infrastructure, as well as relationships between staff differed between the two facilities and were cited as reasons affecting staff intentions to stay or leave. Loosely labelled as “working conditions”, these were perceived to be ‘better’ in the urban-hospital B than rural-hospital A, where staff morale was lower. Geographical differences, including surrounding infrastructure and the availability of services such as schools and recreational facilities, also affected staff decisions and intentions to stay or leave (more pronounced in the rural-hospital A). Opportunities for professional development were also perceived to contribute towards the retention of professional health workers. Conclusion Interviewees emphasized wanting more opportunities for professional development and improving their working and living conditions, as well as improving relationships between the hospitals and district structures. It is important to manage any incentivisation-process (financial and non-financial), including rural allowances and professional staff development, with more caution to ensure that they address the intended goals and do not result in unwanted consequences or tensions. Recommendations Improving conditions in rural areas is indeed a necessary step. Despite the introduction of rural allowances, for health professionals working in rural areas, rural public health facilities still experience a significant shortage of healthcare professional. Further research is needed to pilot and scale-up existing models aimed at promoting staff retention in these public health facilities.
Keywords: Medical Staff